PROMOTING DEMENTIA-FRIENDLINESS IN MANHATTAN, KANSAS - Schuler, Kathleen (My University, 2023)
As the population of people aged 65 and older has increased by both number and proportion, importance has been placed on shaping communities in which seniors can age in place. “Dementia-friendly communities” are communities in which people living with dementia can navigate public spaces safely and be treated with dignity and respect. The Flint Hills Wellness Coalition launched Dementia Friendly Manhattan in 2021 in response to this community need. I worked with Dementia Friendly Manhattan to develop a training curriculum that would be given to any business employees that work with the public. Specifically, businesses that provide essential services such as grocery stores or banks will be targeted. The curriculum focused on dementia awareness, education, signs, and communication strategies. The goal of the training was to make local businesses dementia-friendly and give employees the tools they need to assist customers with dementia. In order to evaluate the effectiveness of this program, I developed a pre- and post-training survey to be administered to trainees. Businesses who participated in the training would receive a certificate of completion that could be displayed at their establishment, as well as a window cling that could be placed in the door or window of their establishment. By creating a recognizable window cling, people living with dementia would be able to easier recognize where they could get help if they need assistance, as well as experience an elevated sense of welcomeness in the community. Additionally, the recognizability of the window cling would encourage other establishments to seek dementia- friendly training so that they could also receive the recognition of being dementia-friendly. This project focused on the social aspect of dementia-friendliness within the community and was meant to improve the quality of life for people living with dementia in Manhattan.
Keywords: Dementia; aging in place; community; dementia-friendly; Dementia Friendly Manhattan